Automated engine calibration validation for real world driving conditions. (26th October 2020) - Fletcher, Tom; Kalantzis, Nikolaos; Cary, Mark; Lygoe, Bob; Pezouvanis, Antonios; Ebrahimi, Kambiz
With the introduction of the WLTP and RDE tests, it has become imperative for automotive manufacturers to verify that their vehicles operate reliably and efficiently across a wide range of operating conditions. Engine air-charge control and torque delivery should be consistent, smooth, and predictable, despite disturbances induced by technologies such as variable cam timing (VCT), exhaust gas recirculation (EGR) and forced induction. This is of particular importance to hybrid and ADAS-enabled vehicles which require accurate control of the engine torque. The validation is an iterative process which can be very time-consuming, expensive and requires considerable experience in order to meet validation criteria. This paper describes the introduction of an automated validation process at the Ford's Dunton Technical Centre in the UK. The automated procedure has been shown to reduce validation process time by around 50% resulting in significant cost-saving whilst improving the overall accuracy of the calibration by around 30-50%.